2005
DOI: 10.1111/j.1365-4632.2005.02623.x
|View full text |Cite
|
Sign up to set email alerts
|

“More is missed by not looking than by not knowing”[Thomas McCrae, 1870–1935]

Abstract: Case 1 A 19-year-old woman presented with a black crust on one part of the tattoo on her right leg ( Fig. 1) which appeared after laser-assisted hair removal by an alexandrite laser (755 nm).Case 2 A 28-year-old man underwent laser-assisted hair removal from his back and shoulders by an alexandrite laser (755 nm), after which he developed a burn on part of the tattoo on his right shoulder and was left with an atrophic scar (Fig. 2).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Consequently, burning and scarring after laser removal do indeed occur in several instances. 16 In a study on the removal of therapy-resistant tattoos, 14 we found textural changes ⁄ scars in 18.8% of treated sites, and Ho et al 15 reported scars in 25% of the cases. Basically, the incidence of scar formation largely depends on adequate treatment settings and especially on sufficient post-treatment wound care.…”
Section: Local Side Effects Of Laser Tattoo Removalmentioning
confidence: 68%
See 1 more Smart Citation
“…Consequently, burning and scarring after laser removal do indeed occur in several instances. 16 In a study on the removal of therapy-resistant tattoos, 14 we found textural changes ⁄ scars in 18.8% of treated sites, and Ho et al 15 reported scars in 25% of the cases. Basically, the incidence of scar formation largely depends on adequate treatment settings and especially on sufficient post-treatment wound care.…”
Section: Local Side Effects Of Laser Tattoo Removalmentioning
confidence: 68%
“…Textural changes are also attributable to hot spots within the laser beam and pulse‐to‐pulse variability. Consequently, burning and scarring after laser removal do indeed occur in several instances 16 . In a study on the removal of therapy‐resistant tattoos, 14 we found textural changes/scars in 18.8% of treated sites, and Ho et al.…”
mentioning
confidence: 68%
“…In addition, such millisecond light devices can unexpectedly cause skin burns when used for hair removal on skin areas covered with a tattoo [17]. …”
Section: Discussionmentioning
confidence: 99%